Who is who in the tropical Atlantic? Functional traits, ecophysiological adaptations and life strategies in tropical calanoid copepods. (February 2019) - Teuber, Lena; Hagen, Wilhelm; Bode, Maya; Auel, Holger
Highlights: Tropical Atlantic copepods exhibit distinct functional traits and life strategies. Functional traits reflect adaptations to food supply and hypoxia in the tropics. A tropical zooplankton community structure is more complex than previously assumed. Abstract: It is well known that tropical oceans harbour a rich biodiversity of calanoid copepods. However, their functional traits, ecophysiological adaptations and life strategies have hardly been studied. In polar, temperate and upwelling ecosystems, calanoid copepods show a variety of specific life strategies in relation to seasonal changes and physical dynamics of their respective habitats. In contrast, it was assumed that epipelagic zooplankton communities in tropical oceans had developed rather uniform life-history traits, due to a low productivity and the lack of a pronounced seasonality. This article reviews ecophysiological characteristics of calanoid copepods from epi- to bathypelagic depths in the eastern tropical Atlantic based on a variety of methodological approaches. Five different types of life strategies could be identified for abundant tropical calanoid copepod species. Pronounced oxygen minimum zones, prominent in many (sub-)tropical regions, are apparently an important driver for the development of copepods' adaptations and life-history traits. Our results emphasize that life strategies of tropical copepods are more complex and diverse than previously assumed. This review clearly identifies certain copepod groups that are better adapted to hypoxia than others and may thus cope with intensifying and expanding oxygen minimum zones in a future ocean.